Implementasi Kurikulum Merdeka dalam Pembelajaran Pendidikan Agama Islam di Paket C PKMB Ar-Rahman Dermo - Arif Nurrahman Hakim (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Education serves as the primary foundation for advancing individuals and societies, playing a vital role in developing potential and improving the quality of human life. The concept of the Free Curriculum has evolved as a new paradigm in the educational process, granting students the freedom to actively participate in designing and directing their learning according to their interests and talents. The implementation of the Free Curriculum in Islamic Religious Education within the context of Equal Education emerges as an intriguing phenomenon that warrants further exploration. The research focus in this study includes: (1) How is the Implementation of the Free Curriculum in Equal Education? (2) What is the Pedagogy of Islamic Religious Education in Equal Education? The objectives of this research are: (1) To understand the Implementation of the Free Curriculum in Equal Education, (2) To understand the pedagogy of Islamic Religious Education in Equal Education. This research employs a qualitative research method to delve into a deeper understanding of students' and educators' experiences in applying the Free Curriculum approach. Furthermore, two major educational theories, namely Carl Rogers' and Hilda Taba's theories, are used as a foundation for analyzing the implementation. The research findings reveal that the implementation of the Free Curriculum in Islamic Religious Education in Equal Education exhibits unique characteristics. The principles of Carl Rogers' theory, such as acceptance, empathy, and student autonomy, are reflected in a more inclusive relationship between students and educators. On the other hand, the analytical approach and curriculum design influenced by Hilda Taba's theory provide a framework that aids in the development of a more structured learning environment. However, this research also identifies several challenges in implementing the Free Curriculum. Among them are the need to enhance educators' competence in designing learner-centric lessons that support student autonomy and the necessity for a deeper understanding of integrating Carl Rogers' and Hilda Taba's principles within the context of Islamic Religious Education.